Experimental Investigation of the Anchoring Effect of Two Different Types of Rock Bolts on Fractured Rock - Rongchao Xu; Hui Zhou (Advances in Materials Science and Engineering)
A deep understanding of the anchoring effect of rock bolts on fractured rock is essential for support design in rock engineering. In this paper, cubic specimens containing a single preexisting flaw with different inclination angles were made by high-strength gypsum; uniaxial compression tests were conducted on bolted and unbolted specimens to study the anchoring effect of the fully bonded bolt and the prestressed bolt on fractured rock. The mechanical parameters and failure characteristics of bolted and unbolted specimens were compared and analyzed in detail. The results indicated that both the prestressed and fully bonded bolt had a significant influence on the mechanical behavior of fractured rock. The average value of E, σi, σp, and σr of bolted specimens all increased due to the effect of the rock bolt. The increase degree was the greatest for the specimens with flaw inclination angle of 45°. The increase in residual strength, σr, was the most significant among all the mechanical parameters. The mechanical parameters of specimens anchored with a prestressed bolt increased with an increase in pretension stress. Besides, the reinforcement effect of the two types of rock bolts was different for different mechanical parameters. The bolted specimens displayed different failure characteristics compared to the unbolted specimens. Variation of tension stress in the prestressed bolt during the loading process was divided into three different stages. With an increase in the inclination angle from 30° to 60°, the peak tension stress value first increased and then decreased and obtained the maximum value at inclination angle of 45°. Besides, the peak tension stress value increased with pretension stress.